Effect of chromium contaminated soil on arbuscular mycorrhizal colonisation of roots and metal uptake by Plantago lanceolata - Estaún, V.; Cortés, A.; Velianos, K.; Camprubí, A.; Calvet, C. (Spanish Journal of Agricultural Research, 2010)
Industrial practices are the primary causes for the accumulation of chromium in the environment, an element considered as a toxic heavy metal when present in high concentrations. The beneficial contribution of arbuscular mycorrhizal fungi (AMF) to plant nutrition and growth has been acknowledged, however, results of heavy metal uptake by plants under mycorrhizal symbiosis vary. The AMF Glomus intraradices (BEG 72) was used with Plantago lanceolata as a host plant in three experiments. In the first one, devised to assess the plant tolerance to Cr(III) in the soil, four levels of chromium concentration were applied in a sterile soil mix, placed in pots with inoculated and non inoculated plant treatments. Plant survival, shoot weight and AMF root colonisation were measured. In the second experiment which was designed in order to determine the effect of the symbiosis on the chromium uptake, similar treatments were used, and in addition, the heavy metal plant tissue content was measured and the bioconcentration factors calculated. In the third experiment the chromium uptake from an industrial chromium waste contaminated soil was assessed using treatments with and without the AMF. Results showed that chromium has a severe impact on the survival of non inoculated plants, however, plants inoculated with AMF in moderately contaminated soil, perform in terms of growth and survival rate, as well as the non inoculated plants in soil with no chromium added, suggesting a buffering effect of the AMF by decreased intake of the toxic element in the roots and its translocation to the shoot.